Assessment of organizational agility: adaptation and validation of the scale for application in turkey - HATUNOĞLU, ŞÜKRÜ BARIŞ (My University, 2022)
Purpose- Organizational agility is a critical dynamic capability necessary for organizations that compete in today’s rapidly changing business conditions. In the literature, there are multiple perspectives to draw the borders for an organization’s ability to be agile. Although Organizational Agility is a well-established concept in studies executed in U.S. and Europe, researches performed in Turkey still lack focus on agility dramatically. In order to fill this gap, this study is intended to adapt and validate the measurement scale of Lee, Sambamurthy, Lim and Wei (2015) to be used for companies operating in Turkey. Methodology- Lee et al. (2015) formed a 12-item scale to measure the components of organizational agility which are “proactiveness”, “radicalness”, “responsiveness” and “adaptiveness”. Items to measure these components are translated into Turkish and reviewed for clarity, comprehensibility and risk of ambiguity by the linguistic professionals and academicians in the field. Finally, the scale is tested on a sample of 320 employees in managerial positions of companies that are operating in Turkey. Findings- 12-item scale is tested through exploratory factor analysis to check for any differences in the items’ distribution between the components of the construct. Four factors are formed parallel to the original scale representing proactiveness, radicalness, responsiveness and adaptiveness. As a consequence of very close factor loadings under two different components, one item from the adaptiveness factor is removed. The reliability values of all factors were above the necessary thresholds in the literature. In order to confirm the results of the EFA, AMOS is used for the confirmatory factor analysis and the results showed a very high model fit. Subsequently, discriminant validity and convergent validity tests are executed showing satisfactory output with no errors. Conclusion- The results show that the scale of Lee et al. (2015) can be used to measure the organizational agility of companies in Turkey. For their future studies, researchers can execute these scales on managerial level employees (since organization-wide information is required) to assess the levels of four dimensions of organizational agility. Keywords: organizational agility, proactiveness, radicalness, responsiveness, adaptiveness
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Yönetim ve Organizasyon; Social Sciences and Humanities; Management; Management and Organization; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; organizational agility; proactiveness; radicalness; responsiveness; adaptiveness